(untitled) (Journal of the College of Education for Women, 2019)
The book of the summary in the control of the laws of Arabic is one of the most important books of Andalusian grammar, the resonance of which is clearly evident among the mother of the language books in the seventh century AH because of the character of the educational style easy and simplified service for anyone who wants the Nile Arabic grammar, that end through what is pursued in his book (Summary) on according to visual standards, as was Ibn Abi Al-Rabeea of first- type, and illustrated in which he addressed the analogies, and he followed the modalities expressed and its consequences relating to each attachment in which a (illness and reasoning factor) And what he said in the framework of each service for the study material in his hands, expressing her terms and manifestations present over the folds of his book. In this way, the scholars and scholars celebrated (not only the Maghreb), but also the Mashreq.The reason for the zigzag in this research is because Ibn Abi Al-Rabee, like other Andalusian scientists, is a great achievement of creativity and science, but in his achievement this book, the summary, has been absent intentionally or unintentionally, despite the abundance of information and the diversity of sources and reference to the Oriental achievement. The research came to be known as the result of this measurement, since it was derived from the origin of the grammar to the difference in proportions between those who took it and who did not take.